Job satisfaction of female office clerks in government, multinational, and local private business concerns of Bangladesh - Rahaman, Afrina; ., Nargis Akhter (Journal of Economics and Behavioral Studies, 2010)
In this study the researchers attempt to make a comparative study among the female office clerks of government, multinational and local private business organizations in Bangladesh regarding their job satisfaction. The study consisted of 255 sample female office clerks of government; multinational and local private business concerns in Bangladesh and convenient method of sampling was used to collect data for this study. Factor analysis, regression analysis were used for analyzing the data. The employers of government, multinational and local private business organizations can take help from this study to know about the job satisfaction of female office clerks of their organizations. The study also opens the scope to make a comparative study on various issues to female office clerks in Bangladesh.